Faktor-Faktor yang Memengaruhi Psikologis Pasien dan Keluarga saat Menerima Bad News tentang Kanker - Febrianty, Indida Leli Indah; Gayatri, Dewi; Rachmawati, Imami Nur (Journal of Telenursing (JOTING), 2024)
This research aims to determine the factors that influence psychology when receiving bad news about cancer. The method uses a systematic review approach on ten journals analyzed using PRISMA. Database search via Springer, Scopus, PubMed, ClinicalKey, and ScienceDirect. The results of a systematic review show that the factors that influence psychological factors are supportive communication, information, nurse presence, environment or privacy, emotional and empathic support, language, stage of disease, family involvement, and demographic characteristics. In conclusion, delivering bad news about cancer must consider factors that can influence the psychology of patients and families. Training related to delivering bad news needs to be given to nurses who provide oncology services to reduce the psychological factors that occur when patients and families receive bad news about cancer. Keywords: Bad News, Cancer, Patients and Families, Psychology